Implementasi Metode Servqual Dalam Sistem Informasi Klinik Afrina Dental Care Berbasis Web - Paranindra Ardhana Biroe Aurori; Raissa Amanda Putri (Universitas Islam Raden Rahmat, Malang, 2024)
Klinik Afrina Dental Care, operating in Simpang Empat District, Asahan Regency since 2006, offers a variety of dental care services. This study aims to improve service quality through the application of the Servqual method in a web-based information system, which measures five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The analysis results indicate that the overall service quality exceeds patient expectations. The